2023
DOI: 10.1186/s13018-023-04034-7
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between bone mineral density and sarcopenia in US adults: a population-based study

Abstract: Introduction In the aging process of the body, in addition to changes in fat and muscle content, there is also bone loss, implying the possibility of a strong muscle–bone–lipid link. In this study, we initially investigated the relationship between lumbar BMD and low muscle mass and the relationship between “muscle–bone–lipid.” Methods The datasets from the National Health and Nutrition Examination Survey (NHANES) 2011–2018 were used in a cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Studies using DXA suggest a negative association of bone mineral density with sarcopenia. ( 14 ) It has also been reported that the dynamic balance between “muscle–bone–lipid” may be associated with the pathogenesis of bone loss. ( 14 ) Our study reveals that the progression from a healthy condition to pre-sarcopenia in older adults results in a lower limb fat index (LFI), which is a novel fat index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using DXA suggest a negative association of bone mineral density with sarcopenia. ( 14 ) It has also been reported that the dynamic balance between “muscle–bone–lipid” may be associated with the pathogenesis of bone loss. ( 14 ) Our study reveals that the progression from a healthy condition to pre-sarcopenia in older adults results in a lower limb fat index (LFI), which is a novel fat index.…”
Section: Discussionmentioning
confidence: 99%
“…( 14 ) It has also been reported that the dynamic balance between “muscle–bone–lipid” may be associated with the pathogenesis of bone loss. ( 14 ) Our study reveals that the progression from a healthy condition to pre-sarcopenia in older adults results in a lower limb fat index (LFI), which is a novel fat index. ( 15 ) Conversely, LFI became higher in the process of progression from pre-sarcopenia to sarcopenia, revealing that sarcopenia progression is associated with fat.…”
Section: Discussionmentioning
confidence: 99%
“…Appendicular skeletal muscle mass (ASM), the sum of the lean mass of extremities, was assessed using dual-energy X-ray (DXA) (QDR Discovery; Hologic, Inc., Bedford, MA, USA). In this study, SP used ASM divided by body mass index (BMI) (ASM/BMI) with cutoff points of ≤ 0.789 in men and ≤ 0.512 in women according to the Foundation for the National Institutes of Health (FNIH) criteria, which widely used in recent research ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal muscle was defined as mass that was neither fat nor bone, and appendicular skeletal muscle mass (ASM) was determined as the total mass of the lean soft tissue of the extremities. Muscle mass was assessed by the ASM index (ASMI) which was determined as the total ASM in kg divided by the BMI in kg/m 2 (24). Low muscle mass was assessed using the ASMI with the cut-off values of ASMI <0.512 for women and < 0.789 for men (5).…”
Section: Assessment Of Body Compositions Dxa and Low Muscle Massmentioning
confidence: 99%